CONTENT OF NATURAL RADIONUCLIDES IN MINERAL NATURAL DRINKING WATER OF ST-PETERSBURG AND LENINGRAD REGION - M. V. Kaduka; L. N. Basalaeva; T. A. Bekyasheva; S. A. Ivanov; N. V. Salazkina; V. V. Stupina; А. N. Kaduka (Радиационная гигиена)
The aim of the study was to estimate the radiation characteristics of the mineral natural drinking table and medical-table water, consumed by the population of St-Petersburg and Leningrad region. This study was focused on the bottled natural mineral drinking water, available in St-Petersburg and Leningrad region market, as well as on the natural mineral drinking water sampled from the St-Petersburg groundwater supplies. Data on the levels of radionuclides specific activities in the sources under investigation was obtained using radiochemical analysis with the subsequent radiometric or spectrometric measurement of the counting samples. 107 samples of mineral natural drinking water were analyzed during the period from1999 till the December of 2017. Assessment included estimation in different combinations of the levels of gross alpha- and beta activities, specific activities of 226Ra, 224Ra, 228Ra, 210Pb, 210Po, 238U, 234U, 40K and 222Rn, as well as the estimation of the index of conformance of the water to the requirements of the radiation safety. The mentioned index is the sum of the ratios of the specific activities of the individual radionuclides to the corresponding guidance levels. Exceedance of the index of conformance for the gross alpha-activity was detected for 87% of analyzed water samples; for the gross beta-activity – for 18% of the samples. Exceedance of the index of conformance of the water to the requirements of the radiation safety was detected for 40% of the analyzed samples. Exceeding of the guidance level of radionuclide in drinking water was found: in 24% water samples for 226Ra concentration, in 24% – for 228Ra concentration, in 3,5% – for 224Ra concentration. An exceedance of the guidance levels for 210Pb, 210Po, 238U, 234U, 40K and 222Rn in analyzed samples was not detected. The main contribution to the sum of the ratios of the specific activities of the natural radionuclides to the corresponding guidance levels and, correspondently to the exposure dose to the population of St-Petersburg and Leningrad region from the consumption of the mineral drinking water give 226Ra, 228Ra and 222Rn the total contribution of which to the mentioned value exceeds 90%.